Crushing and grinding at Amax's Sleeper gold mine - J. J. DeMull; B. A. Boster (Society for Mining, Metallurgy & Exploration, 1990)
Amax's Sleeper mine uses conventional cyanidation milling and heap leaching techniques to produce gold. Since milling operations commenced in March 1986, average ore processing rates have improved from the design rate of 455 t/d (500 stpd) to more than 720 t/d (795 stpd). Heap leaching was added to the process facilities in September 1986 at a design rate of 1.5 kt/d (1650 stpd) and current heap leaching rates exceed 2.7 kt/d (2950 stpd). Presented are descriptions of the Sleeper processing facilities with emphasis on the crushing and grinding circuits, a review of the selection of crushing and grinding equipment, and a summary of operating performance during the first 16 months of operations.